Assessing the efficacy of TNF‐alpha inhibitors in preventing emergency and emergent colectomies. Issue 2 (2nd August 2019) - Rajan, Ruben; Trinder, Matthew W; Lo, Johnny; Theophilus, Mary
Abstract : Background and Aim: Severe ulcerative colitis (UC) is potentially life threatening and is associated with significant morbidity. TNF‐∝ inhibitors (Infliximab) were introduced in Australia for the management of medically resistant, acute, severe flares of UC in 2008. The aim of this study is to assess the efficacy of Infliximab in preventing emergent and emergency colectomies for patients with moderate to severe UC by comparing colectomy rates before and after its introduction at our institution. Methods: This was a retrospective cohort study of all patients who were admitted to the Royal Perth Hospital with a flare of UC between 2002 and 2017. Patients were divided into two cohorts: those admitted prior to the introduction of Infliximab (pre‐2008) and those admitted after. We compared data between these two groups, including age, gender, length of admission, use of Infliximab, colectomy, and complications of surgery. We defined emergency surgery as requiring surgery during the index admission and emergent surgery as an operation within 54 weeks. Results: A total of 313 UC cases from 2002 to 2017 were analyzed. There was a decrease in emergency and emergent colectomies from 19.4 to 8% in the post‐2008 cohort ( P = 0.008). Furthermore, there was a decrease in the proportion of operations performed as emergencies, from 36 to 20%. This resulted in a significantly reduced length of stay (13.4–9.7 days, P < 0.05) and complication rate (36 to 20%, P < 0.05). Conclusion: Overall, the need for emergency and emergent operations has drastically reduced at our institution with the introduction of Infliximab. This study has confirmed the efficacy of Infliximab in reducing colectomy rates at our institution. Abstract : This is a retrospective cohort study that compared the rates of colectomy for severe ulcerative colitis over a 15‐year period before and after the introduction of Infliximab therapy at our institution. We found a significant decrease in the rates of colectomy for severe ulcerative colitis over the study period, as well as a reduction in the rates of complications.